A revised chronology for the Zhizo and Leokwe horizons at Schroda - Antonites, Annie R. (Southern African Humanities, 2018)
Schroda, a Zhizo/Leokwe settlement in the Limpopo Valley, is well known among archaeologists who study the rise of complex societies in southern Africa. Previous research placed the site at the centre of early East Coast trade networks with the southern African interior, elevating it to economic and socio-political prominence in the region during the AD 900s. By AD 1000, Schroda’s influence had declined due to a shift in regional socio-political dynamics linked to the establishment of K2. These regional developments coincided with a change from the Zhizo to Leokwe ceramic styles, which has been used to establish a multicomponent occupation at Schroda. However, the identification of different depositional horizons was limited to one of six excavated areas at the site. Through an integrated analysis of ceramic style traits, glass bead sequences and original stratigraphic descriptions, this study presents a revised chronology for the five largest excavated areas at Schroda. The updated chronologies place the excavated material within its correct historical context and enable phase-specific comparisons of all material culture from Schroda. Five new radiocarbon dates inform on the timing of the Zhizo/Leokwe transition and the abandonment of the site. KEY WORDS: Early Farming Communities, Iron Age, Limpopo Valley, ceramics, radiocarbon dates.